2015
DOI: 10.1136/bmjopen-2015-008298
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of adverse drug reactions to antiepileptic drugs in children

Abstract: ObjectivesTo prospectively determine the nature and rate of adverse drug reactions (ADRs) in children on antiepileptic drugs (AEDs) and to prospectively evaluate the effect of AEDs on behaviour.SettingA single centre prospective observational study.ParticipantsChildren (<18 years old) receiving one or more AEDs for epilepsy, at each clinically determined follow-up visit.Primary and secondary outcomesPrimary outcome was adverse reactions of AEDs. Behavioural and cognitive functions were secondary outcomes.Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
56
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 39 publications
8
56
1
1
Order By: Relevance
“…Similar observations have been reported by Shobhana Mathur et al 12 Also similar results have been reported by other studies also. [13][14][15] This shows that the pattern of pharmacological therapy for epilepsy in these studies was similar to our study.…”
Section: Discussionsupporting
confidence: 84%
“…Similar observations have been reported by Shobhana Mathur et al 12 Also similar results have been reported by other studies also. [13][14][15] This shows that the pattern of pharmacological therapy for epilepsy in these studies was similar to our study.…”
Section: Discussionsupporting
confidence: 84%
“…These studies have identified ADRs in 4.67%-31% in patients receiving different AEDs. [8][9][10][11][12] There is a scarce in the published data regarding the incidence and pattern of ADRs to different AEDs in the local population. With this background, the main aim of the study was to identify and evaluate the ADRs associated with different antiepileptic drugs based on preventability, predictability and severity.…”
Section: Introductionmentioning
confidence: 99%
“…In a prospective study, Anderson et al 15 reported a significantly higher risk of adverse drug reactions (ADRs) in children receiving polytherapy than monotherapy. Aggregated safety reports for lamotrigine in children have also shown that the risks of developing most ADRs are lower with monotherapy than polytherapy 16.…”
Section: Monotherapy or Polytherapy In Epilepsy Managementmentioning
confidence: 99%